Variabilitas Suhu Dan Klorofil Saat Terjadi Fenomena Upwelling Di Perairan Selatan Pulau Buru Hingga Pulau Seram - Simon Tubalawony; Ana Yeti Huwae (Universitas Mataram, 2024)
Upwelling is the rise of water mass in the lower layer to the surface. The rise of water mass is due to wind moving above the waters so that this wind will push the water mass on the surface as a result of which water from below replaces the emptiness above. The variation in SST distribution is relatively lower and the abundance of chlorophyll as an indicator of the occurrence of the upwelling phenomenon and the effect of wind on the upwelling phenomenon. The purpose of this study was to determine the variability of SST and chlorophyll in the waters of South Buru Island to Seram Island and its effect on the upwelling phenomenon. The method used is a quantitative method with the aim of describing the state of SST and Chlorophyll in the Waters of South Buru Island to Seram Island. The results of the study showed that the analysis of the distribution of SST and chlorophyll from June to October was an upwelling phenomenon with SST in June 28.15 ° C and chlorophyll-a 0.44 mg / m3 with an average wind speed of 4.58 m / s which was the beginning of the upwelling phenomenon. For July, the SST distribution was 27.21°C and chlorophyll-a 0.54 mg/m3 with an average wind speed of 5.42 m/s. In August, the SST distribution was 26.95°C and chlorophyll-a 0.58 mg/m3 with an average wind speed of 5.32 m/s. In September, the SST distribution was 27.73°C and chlorophyll-a 0.50 mg/m3 with an average wind speed of 4.09 m/s, while in October, the distribution was 28.97°C and chlorophyll-a 0.29 mg/m3 with an average wind speed of 2.65 m/s.